2020
DOI: 10.3389/fonc.2020.00336
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Patterns of Perirenal Fat Invasion Are Associated With a Poorer Prognosis Compared With Isolated Invasion: A Proposal for a Revision of T3aN0M0 TNM Staging System

Abstract: Objectives: Currently, renal cell carcinoma (RCC) presenting with perisinus fat invasion (PSI) and/or perinephric fat invasion (PFI) is merged as one entity, pathological T3a (pT3a); however, the combination of PFI and PSI (PFI+PSI) may not be associated with equivalent prognosis compared with either PFI or PSI alone (PFI/PSI). Here, we analyzed the prognostic significance of PFI+PSI vs. PFI/PSI in pT3aN0-1M0-1 RCC.Method: We identified 5,290 patients with pT3aN0-1M0-1 RCC, treated by nephrectomy, from the Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…We further conducted a sensitivity analysis including the data of T3aNanyMany and found that stratification for T3a RCC with a cutoff of 4 cm and 7 cm still showed a good predictive accuracy (c‐index: 0.781, data not shown). Another study by our group showed that multiple patterns of perirenal fat invasion are associated with a poorer prognosis than isolated invasion, which was consistent with previous studies 15 . Therefore, there is a need to further refine the reclassification for T3a RCC to increase the ability to predict prognosis and integrate tumor size and perirenal fat invasion types in future investigations.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We further conducted a sensitivity analysis including the data of T3aNanyMany and found that stratification for T3a RCC with a cutoff of 4 cm and 7 cm still showed a good predictive accuracy (c‐index: 0.781, data not shown). Another study by our group showed that multiple patterns of perirenal fat invasion are associated with a poorer prognosis than isolated invasion, which was consistent with previous studies 15 . Therefore, there is a need to further refine the reclassification for T3a RCC to increase the ability to predict prognosis and integrate tumor size and perirenal fat invasion types in future investigations.…”
Section: Discussionsupporting
confidence: 89%
“…The current definition of T3a RCC is tumor grossly extends into the renal vein or its segmental (muscle‐containing) branches or tumor invades perirenal and/or renal sinus fat (peripelvic fat), but not beyond Gerota fascia. The three types of T3a infiltration (renal vein infiltration, perirenal fat, and renal sinus fat infiltration) may have their prognostic differences, and there are some pieces of evidence to prove this point 14‐16 . One of the most classic studies is from Shah's research, 14 they found that the presence of multiple patterns of extrarenal extension (renal vein infiltration, perirenal fat, and renal sinus fat infiltration) is associated with a higher risk of disease progression and RCC‐related death after RN compared to isolated involvement of the renal vein infiltration, perirenal fat, and renal sinus fat infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasion into perirenal fat has been shown to not increase RCC-speci c mortality. Conversely, invasion into sinus fat portends a worse prognosis than perirenal-fat invasion even though both are classi ed as T3aN0M0 [23][24][25]. We found that RCC presenting with sinus/perisinus-fat invasion could not bene t from PN regardless of tumor size.…”
Section: Discussionmentioning
confidence: 66%
“…Our understanding of the heterogeneous behavior of renal tumors has been well advanced. The increasing interest in adjuvant treatment, immunotherapy and targeted therapies has prompted the need for more accurate staging of renal tumors (5)(6)(7)(8)(9). In the clinical context, some pT3a renal tumors are confirmed by postoperative pathology, and their incidence is usually underestimated.…”
Section: Introductionmentioning
confidence: 99%